Wybrane problemy dystrybucji mebli wytwarzanych w Polsce na rynku Unii Europejskiej - Adamczuk, Franciszek (Selected Issues of Distribution of Polish Furniture on European Union Market, 2008)
The aim of the paper is to present the basic issues of distribution of Polish furniture on international market. The European Union market is chosen as the subject of the analysis. After a short theoretical introduction, the author presents the conditions of European furniture market and the Polish market in the context of European Union requiments. The conclusion of this paper could contribute to the improvement of the distribution of Polish furniture on the European market.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 11, s. 219-228